2019
DOI: 10.3390/v11060545
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Full-Length gag Gene from the Earliest Korean Subclade B of HIV-1: An Outbreak among Korean Hemophiliacs

Abstract: We determined the earliest full-length HIV-1 gag gene sequences in 110 patients with HIV-1, including 20 hemophiliacs (HPs) and 90 local controls (LCs). The gag gene from stored sera was amplified using RT-PCR, and was subjected to direct sequencing. Phylogenetic analysis indicated that 94 and 16 sequences belonged to the Korean subclade of HIV-1 subtype B (KSB) and subtype B, respectively. A total of 12 signature pattern amino acids were found within the KSB, distinct from the worldwide consensus of subtype B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(30 citation statements)
references
References 21 publications
(86 reference statements)
3
27
0
Order By: Relevance
“…The clinical characteristics of all patients were described in previous studies [ [2] , [3] , [4] , [5] , 19 ]. They all were infected with KSB from Plasma Donors O and P [ [2] , [3] , [4] , [5] , 19 ], and the earliest vif genes from Plasma Donors O and P were all wild-type (WT) ones [ 3 ]. In addition, we had obtained vif - vpr genes in the two plasma donors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical characteristics of all patients were described in previous studies [ [2] , [3] , [4] , [5] , 19 ]. They all were infected with KSB from Plasma Donors O and P [ [2] , [3] , [4] , [5] , 19 ], and the earliest vif genes from Plasma Donors O and P were all wild-type (WT) ones [ 3 ]. In addition, we had obtained vif - vpr genes in the two plasma donors.…”
Section: Resultsmentioning
confidence: 99%
“…The twenty patients with hemophilia (HP), identified in this study as HP 1–HP 20, were diagnosed with HIV-1 infection between 1990 and 1994 ( Table S1 ) [ [2] , [3] , [4] , [5] , 19 ]. They had been treated primarily with imported clotting factors before the start of local domestic clotting factor production .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously conducted a nationwide genetic analysis of HIV-1 with sera from individuals in the early stages of HIV-1 infection (before 1994) to identify the cause of an HIV-1 outbreak among patients with hemophilia in Korea in 1990-1994. These molecular epidemiological studies revealed that viruses from two cash-paid plasma donors were incompletely inactivated in the process of manufacturing clotting factor IX and were identified as the agents of infection among 20 HIV-1-infected patients with hemophilia and HIV-1 infection [1][2][3][4][5][6]. The viruses in 8 and 12 patients with hemophilia infected with the Korean subclade of HIV-1 subtype B (KSB) originated from plasma donors O and P, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The viruses in 8 and 12 patients with hemophilia infected with the Korean subclade of HIV-1 subtype B (KSB) originated from plasma donors O and P, respectively. In these studies [1][2][3][4][5][6][7], we conducted an in-depth analysis by genes, but a few genes are yet to be studied. The sequence length significantly affects the extent of clustering in a phylogenetic tree [8][9].…”
Section: Introductionmentioning
confidence: 99%